ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI KOPI di INDONESIA - SALMA KURNIA (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2023)
Every country in the world has natural resources that can be used to support the country's economic growth. One of them is Indonesia, Indonesia is a country that has the most natural resources in the world. Indonesia is an agricultural country where most of the population works in agriculture. Plantation commodities are Indonesia's leading export, which makes Indonesia the third country as the largest coffee exporting country with a market share of 7%. Coffee is one of the main sources of state income, from plantation products with global commodities of high economic value. So that researchers want to analyze the factors that influence coffee production in Indonesia using secondary data obtained from BPS. The results of the coefficient of determination test (R-Squared) concluded that the relationship between coffee production variables could be explained by the fertilizer variable and the farmer's exchange rate of 38% while the remaining 62% was explained by other variables outside the model.